"I'm Not a Man. I Don't Want to Destroy You": Tolstoy College and LGBTQ Studies in the Vietnam War Era. Issue 4 (14th June 2018) - Wilson, Jennifer
Abstract: This article profiles Tolstoy College (1968–84), an experimental academic community built on the anarchist and antiwar principles of the nineteenth-century Russian novelist Lev Tolstoy. Tolstoy College existed within the State University of New York (SUNY) at Buffalo and was part of a university-wide initiative to channel the growing radicalism of the student body (a radicalism nurtured by the Vietnam War protests and the American civil rights movement) into institutionalized academic spaces. Beginning as the locus on campus for opposition to the war and a space where returning Vietnam War veterans could receive support, Tolstoy College eventually transformed, offering a wealth of courses on the gay-male experience and becoming the Buffalo headquarters for the Gay Liberation Front. This article explores that development, tracing how a critique of masculinity and militarism served as the bridge between antiwar principles and commitment to gay liberation. Though it was eventually dissolved in the mid-1980s, Tolstoy College provides important and understudied insights into how opposition to the Vietnam War contributed to the development of LGBTQ studies on college campuses.